Venture-building-as-a-service: a third-party approach to venture building: case research of big corporations in Brazil - Melo, Giuliana Siqueira Guedes de (2025)
The adoption of innovation strategies by large and established businesses has been a worldwide growing trend in the past decade. These corporations, especially multinationals, started to perceive the threats of the startup ecosystem and the speed that new technologies and business models have been created. To stay ahead of the curve and maintain a competitive edge, these companies have been engaging in corporate venturing activities to foster entrepreneur initiatives, gain exposure to disruptive technologies, access new markets and diversify their revenue streams, among many other reasons. An increasingly important strategy in the open innovation landscape is corporate venture building, which involves creating new and independent ventures that serve as a hub for innovation. Instead of passively investing in startups, big corporations engaging in external venture building initiatives aim to develop new businesses that are aligned with the parent companies’ strategic imperatives, while using existing resources and benefiting from unencumbered corporate bureaucracy. The mechanism provides the large corporations innovation at the speed, flexibility, and agility of a startup, increasing their chances of succeeding. This research examines the process of new venture building through a third-party approach, focusing on two ventures developed by the Brazilian corporate venture builder Play Studio, in partnership with two distinct big corporations in Brazil. The objective of this study is to answer the question of how venture-building-as-aservice has driven corporate innovation and value creation in two specific projects. It follows the structure of descriptive and exploratory single-case research design. Firstly, it identifies the key concepts in developing a new venture within a big corporation setting and startup ecosystem, elaborating common structures and processes when engaging with this innovation mechanism. Second, the paper explores and examines the corporate venturing landscape in Latin America and Brazil, with both qualitative and quantitative data. Third, it analyzes the case research in depth and explores the process of venture building by using multiple sources of evidence and points of view discussed from different lenses. The comparison between different corporate venture building initiatives in companies with different organizational attributes is developed with the purpose of providing the reader with two different scenarios, identifying common practices and the key success factors to be considered when engaging with this innovation mechanism. The key findings of this research show that the process of venture building is flexible, and the methodology is adapted to different organizational attributes. Both companies present as key success factors the autonomy for venture builders to execute the project, the combination of external expertise and internal resources, as well as the topmanagement strategic oversight and collaborative involvement of internal departments. Thus, this study provides valuable insights for practitioners and researchers on new business building’ concepts and processes by means of venture-building-as-a-service.